Agrarian Reform and National Land Law Political Policy Provide Legal Assurance for Investment - I Made Pria Dharsana; I Nyoman Putu Budiartha; I Made Setiasa (Fakultas Hukum, Universitas Warmadewa, 2023)
The provision contained in Article 33 paragraph (3) of the 1945 Constitution of the Republic of Indonesia (UUDNRI) as the initial milestone in the birth of Law No.5 of 1990 concerning Basic Agrarian Regulations or better known as the basic Agrarian Law (UUPA). This research was designed using normative legal analysis with a statutory and conceptual approach. These two approaches are used to develop arguments, especially to answer the legal issues raised in this study. The result shows that The land law itself is a law that regulates the rights to control the land or the surface of the earth. The development of land law politic cannot contradict the essence of state goals that have been regulated in the state goals is regulated in the 1945 Constitution, where Pancasila as the basic norm that gave birth to the preamble provisions in the 1945 Constitution. Speaking about the agrarian reform, according to the national agrarian law, the goal is to make a fair and equitable distribution on the source of the livelihood of farmers in the form of land, so that with the distribution it is hoped that fair and equitable result can be achieved.